Augmented reality navigation systems in endoscopy - Metzger, Rebecca; Suppa, Per; Li, Zhen; Vemuri, Anant (Frontiers in Gastroenterology, 2024)
Navigation assistance has become part of our daily lives and its implementation in medicine has been going on for the last 3 decades. Navigation is defined as the determination of a position in space in the context of its surroundings. While routing applications used in cars highlight the street to follow, in medical applications the real-world perception of the user is enriched by digital elements that provide guidance and help the user navigate. Unlike Virtual Reality (VR) solutions, which are mainly used for training, Augmented Reality systems (AR) do not require the user to wear specific headsets/goggles, but the virtual elements are overlaid over the real image displayed on a monitor. Depending on the application and the indication, there are large differences in how much these solutions have entered clinical routine. Especially in the fields of GI endoscopy and laparoscopy, AR navigation solutions are less prominently employed in clinical practice today and still hold significant potential to elevate patient care by improved physician support. This review touches upon why AR navigation systems are currently just starting to become implemented in the GI/laparoscopic clinical routine and which applications can be expected in the GI endoscopy and laparoscopy field. By taking the practitioner’s perspective and following the intuitive navigation workflow, it gives an overview of major available and potential future AR-applications in the GI endoscopy and laparoscopy space, the respective underlying technologies, their maturity level and their potential to change clinical practice.